Heterogeneity of Recent Phase 3 Complicated Urinary Tract Infection Clinical Trials. (2nd February 2021) - Portsmouth, Simon; Bass, Almasa; Echols, Roger; Tillotson, Glenn
Abstract: Background: For new antibiotics developed to treat antibiotic-resistant Gram-negative infections, the US Food and Drug Administration (FDA) regulatory pathway includes complicated urinary tract infection (cUTI) clinical trials in which the clinical isolates are susceptible to the active control. This allows for inferential testing in a noninferiority study design. Although complying with regulatory guidelines, individual clinical trials may differ substantially in design and patient population. To determine variables that impacted patient selection and outcome parameters, 6 recent cUTI trials that were pivotal to an new drug application (NDA) submission were reviewed. Methods: This selective descriptive analysis utilized cUTI trial data, obtained from publicly disclosed information including FDA documents and peer-reviewed publications, from 6 new antibiotics developed to treat multidrug-resistant Gram-negative infections: ceftolozane-tazobactam, ceftazidime-avibactam, meropenem-vaborbactam, cefiderocol, plazomicin, and fosfomycin. Eravacycline was not approved for cUTI and is not included. Results: Microbiologic modified intent-to-treat sample size, age, proportions of female patients, acute pyelonephritis (AP), Escherichia coli and other pathogens at baseline, protocol-specified switch to oral antibiotic, and the noninferiority margin were compared. Outcome data included clinical response, microbiologic eradication, and composite outcomes, including a subset of patients with AP. Conclusions: A study design can follow regulatory guidelines but still have variable populations. The proportion of AP within a study varied greatly and influenced population demographics (age, gender) and baseline microbiology. A smaller proportion of AP resulted in an older patient population, fewer females, less E coli, and lower proportions of patients achieving success. Fluoroquinolones and piperacillin/tazobactam should be reconsidered as active comparators given the high rates of resistance to these antibiotics. Abstract : In cUTI trial data from 6 new antibiotics targeting MDR Gram-negative infections, proportion of acute pyelonephritis (AP) varied; influencing population demographics and baseline microbiology. Smaller proportion of AP resulted in older patient population, fewer females, less E coli, and lower treatment success.